From competing intermolecular interactions to crystal engineering of new materials : theory and experiment - Panikkattu, Vinu Varghese (Kansas State University, 2022)
In order to study the as of yet unexplored competition between halogen bonds (XB) and chalcogen bonds (ChB) attached to the same molecular skeleton, a series of 4,7-bis(haloethynyl)benzo-1,2,5-chalcogenadiazoles capable of forming competing ChB and XB dimers were designed, synthesized and analyzed crystallogrpahically. Quantum mechanical calculations were carried out on all targets to provide further insight, and to try to predict the experimental outcome of these competing interactions. The computational results aligned perfectly with crystallographic outcomes, predicting a XB dimer to exist in only one out of twenty-four targets, and correctly calculating halogen bond lengths, angles and intramolecular bending angles. The ChB synthon was further employed in providing a template towards the design of multicomponent crystals. The 4 and 7 position substituted haloethynyl species were replaced with different acceptor molecules, which could then bind to bond donors on co-formers towards the formation of co-crystals. Liquid assisted grinding with fifteen co-formers showed excellent success rates towards the formation of co-crystals, and two crystal structures obtained showed that using carboxylic acid co-formers retains the ChB dimer as intended. Stronger halogen bonds lead to better synthon robustness, which in turn contribute to improved supramolecular synthesis reliability. With this in mind, a triple activation strategy was explored to design a library of triply activated ketones with among the highest reported σ-hole potentials, which are used as a yardstick for the halogen bond donor ability of the iodine atom. Computational calculations were carried out to rank the molecules relative to each other and to benchmark them with literature, which confirmed they outperform previously reported molecules. The targets were subsequently synthesized and crystallized, and the single crystal structures of these targets confirmed that they can indeed form strong halogen bonds as the primary structure-directing motif. The ketones were then used as building blocks for supramolecular co-crystal synthesis. A co-crystal screening with thirty-five co-formers revealed an overall 64% success rate in the formation of co-crystals. A total of nine co-crystal structures were obtained, and these further confirmed the strength and structure directing influence exerted by these highly activated halogen-bond donors. In order to further test the robustness of the triple activation design strategy, a library of triply activated ester targets was assessed computationally and experimentally. Computational calculations showed that they slightly outperform the triply activated ketones in terms of σ-hole potentials and are superior to previously reported molecules. After they were synthesized and crystallized, the crystal structures once again confirmed their ability in forming strong structure directing halogen bonds. To confirm that this new library too can be employed towards the formation of co-crystals, a co-crystal screening with thirty-three co-formers revealed an overall success rate of 76%, even higher than the 64% success rate of the triply activated ketones. A total of eight co-crystal structures were obtained, once again including for all targets with phenazine. Computational calculations were carried out to rationalize the 1:1 vs. 1:2 stoichiometric halogen bonds formed by different targets with phenazine. Results revealed that only very high σ-hole potentials can lead to the formation of a 1:2 stoichiometric halogen bonding synthon, further articulating the importance of the strength of the interaction and its resultant ability to direct complex supramolecular assemblies.
Keywords: Halogen bond; Chalcogen bond; Crystal engineering; Co-crystal; σ-hole; Hydrogen bond